(untitled) (Research, Society and Development, 2021)
The genus Struthanthus Mart. are mistletoes known for their harmful characteristics and its germination occurs on the branches of its hosts. The present work aimed to analyze the germination of S. marginatus (Desr.) G.Don on Poincianella pluviosa (DC.) L.P.Queiroz (Fabaceae) growing in the afforestation of the campus of Vitória da Conquista of the Universidade Estadual do Sudoeste da Bahia. Fruits were evaluated for dimensions (n = 10), moisture content (n = 50), and fixed to the host by viscine (n = 60), and accompanied from August 31 to November 06, 2018. The diaspores were 0.75‒0.90 × 0.41‒0.61 cm, with humidity of 58.01% in the seed and 48.79% in the pericarp. In the 30 seeds, the germination started on the 16th day, with a peak on the 20th day. Of these, 40% (n = 12) germinated, one (3%) formed a seedling on the 34th day, dying on the 48th. In the next planting (n = 30), 11 germinated on the 3rd day, peaking on the 6th day, seven formed seedling until the 20th day, dying on the 35th. Our observations show a low germination rate for S. marginatus.